Advanced oesophago-gastric adenocarcinoma in older patients in the era of immunotherapy. A review of the literature. (November 2021) - de la Fouchardiere, C.; Decoster, L.; Samalin, E.; Terret, C.; Kenis, C.; Droz, J.P.; Coutzac, C.; Smyth, E.
Highlights: Older patients (≥70 years) represent more than half of the oesogastric cancer (OGC) incidental population. They are largely under-represented in clinical trials. Reduced-dose chemotherapy with oxaliplatin can be administered in older frail patients. No specific data with immune checkpoint inhibitors are available in older frail patients with OGC. Abstract: Gastric (G) and gastro-esophageal junction (GEJ) adenocarcinomas are of the most common and deadly cancers worldwide and affect mainly patients over 70 years at diagnosis. Older age has been associated in gastric cancers with distal tumour location, well-differentiated adenocarcinoma and microsatellite instability and is not identified itself as an independent prognostic factor. As immune checkpoint inhibitors recently changed the landmark of advanced G and GEJ adenocarcinomas treatment, we decided to perform a literature review to define the evidence-level of clinical data in older patients. This work underlined the lasting low -inclusion rate of older patients and -implementation rate of frailty screening tools in clinical trials in G/GEJ carcinomas. In the first-line metastatic setting, two prospective randomized phase III studies have specifically assessed the efficacy of chemotherapy in older patients with HER2-negative gastric cancers, demonstrating the feasibility of reduced dose oxaliplatin-based chemotherapy regimen in this population. Only few data are available in HER2-positive tumors, or in the second-line setting. Furthermore, no specific trial with immune checkpoint inhibitors was performed in older frail patients whereas their benefit/adverse events ratio make them attractive candidates in this patient's population. We conclude that older fit patients can be treated in the same way as younger ones and included in clinical trials. Improving the outcome of older frail patients should be the oncology community next focus by implementing targeted interventions before initiating cancer therapy and designing specific clinical trials. Frailty screening tools and geriatric data collection have to be implemented in routine-practice and clinical trials.